54.0k views
1 vote
Write each expression in expanded form. Then rewrite the product in exponential form.Only do A, B, and C

Write each expression in expanded form. Then rewrite the product in exponential form-example-1

1 Answer

4 votes

Write each expression in expanded form.

(a)


\begin{gathered} 4^{3\text{ }}.4^4=4^3*4^4 \\ =4*4*4*4*4*4*4 \end{gathered}

(b)


\begin{gathered} (-3)^5.(-3)^{2\text{ }}=(-3)^5\text{ }*(-3)^2 \\ =(-3)^{}*(-3)^{}*(-3)^{}*(-3)^{}*(-3)*(-3)*(-3) \end{gathered}

(c)


\begin{gathered} (-2)^8.(-2)^7=(-2)^8\text{ }*(-2)^7 \\ =(-2)^{}*(-2)\text{ }*(-2)^{}*(-2)*(-2)*(-2)*(-2)*(-2)*(-2)*(-2)*(-2)*(-2)*(-2)*(-2)*(-2) \end{gathered}

Rewriting in exponential form

(a)


\begin{gathered} 4^3.4^4=4^(3+4) \\ \text{ = 4}^7 \end{gathered}

(b)


\begin{gathered} (-3)^5.(-3)^2=(-3)^(5+2) \\ \text{ = (-3)}^7 \end{gathered}

(c)


\begin{gathered} (-2)^8.(-2)^7=(-2)^(8+7)\text{ } \\ =(-2)^(15) \end{gathered}

User TuanDT
by
4.7k points